2014
DOI: 10.1080/08841241.2014.911790
|View full text |Cite
|
Sign up to set email alerts
|

Selling college: a longitudinal study of American college football bowl game public service announcements

Abstract: Using ideological analysis as a frame, researchers analyzed institutionally created commercials (PSAs) that appeared in 28 U.S. college football bowl games over a seven-year period (2003)(2004)(2005)(2006)(2007)(2008)(2009) to better understand the universities' brands as represented in these advertisements. They found many common elements such as showing traditional architectural elements (e.g., clock towers, grounds), highlighting areas of institutional excellence (e.g. rankings), and connecting attendance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Combined, these symbols communicated to outsiders that these were ‘serious’ academic institutions. Again, this is a finding consistent with the existing American higher education marketing literature (Harris, ; Tobolowsky and Lowery, ), where academic rigour has been found to be a commonly touted institutional characteristic.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Combined, these symbols communicated to outsiders that these were ‘serious’ academic institutions. Again, this is a finding consistent with the existing American higher education marketing literature (Harris, ; Tobolowsky and Lowery, ), where academic rigour has been found to be a commonly touted institutional characteristic.…”
Section: Resultssupporting
confidence: 89%
“…Research also finds that academic rigour is touted through the announcement of prestigious academic awards, grants and fellowships acquired by institutional members (Harris, ; Pizarro Milian and Davidson, ), as well as espoused through mission statements which cite institutional ambitions to conduct world‐class research (James and Huisman, ; Kuenssberg, ; Creamer and Ghoston, ; Giusepponi and Tavoletti, ). Rigour is often complemented within promotional materials with what Tobolowsky and Lowery () term as notions of a ‘rich’ life, consisting of a more holistic and enriching experience—including athletics and other social activities (also see Hite and Yearwood, ; Clayton et al ., ; Davidson, ). The overarching story that emerges from the literature is that higher education organisations market themselves by promising a ‘complete’ experience, rather than simple labour market success.…”
Section: Marketing In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the BLR results indicated that FMA had no statistical effects on donations, highlighting the negative effects of the 2008 global financial crisis, especially for younger college football programmes that have not yet developed a large pool of alumni to count on for donations. Second are the discussions relating to FMA and brand revenues which were positively associated (0.256, p < 0.01)validating previous studies that attest to how college football brands may be enhanced and built through winning traditions (Harris, 2009;Tripathi, 2015;Tobolowsky and Lowery, 2014). The BLR results indicated that FMA had a positive statistical effect on branding, indicating the benefits of longevity that come as a result of being well known.…”
Section: Discussionsupporting
confidence: 80%
“…PSE organizations have also been found to showcase orthodox physical features. Tobolowsky and Lowery (2014), for example, found that university commercials typically "showed expansive, beautifully manicured, and lush campus grounds, which provided the lure of curb appeal" (p. 85). As Saichaie and Morphew (2014) argue, the degree of consistency in depictions of physical facilities displayed across promotional materials is a "testament to the institutionalized notion of what prestigious colleges and universities look like" (p. 525).…”
Section: New Institutionalism and Marketing Within Psementioning
confidence: 99%